Encountering, Experiencing and Shaping Careers Thinking About Careers in the 21st Century - Brewer, Ann M. (Springer International Publishing, 2018)
This book investigates how people encounter, experience and shape their careers. Both the concept and the reality of a career is changing as organisations respond to globalisation and market forces. This impact is reflected in the internal labour market and hence career journeys of individuals. How people think about their career and career choices is more diverse than ever before due not only to environmental transformations but also to variations in the workforce, consisting now of five generations. With each new generation, there is little argument that contemplating career choices, seeking and promoting work opportunities as well as hiring relationships are now markedly different and less certain than previously. People have now and increasingly a greater choice over when, where, how to work and for how long. This book will provide learning for those people early in their careers as well as those in mid to later career, looking to develop or enrich their careers in some way. Understanding how work functions in people's lives; the personal and family costs incurred in maintaining and exiting a career, and how and why remaining or leaving a career is successful or not, is highly relevant. The need for career support, derived from personal, professional and organisational connections plays an important role in career choice, career transition, and career opportunities. Creativity and other 21st century skills, the vital dimensions of career development, is also discussed in this book. .